Modular plug-in high-performance assembly of a power converter - Solomon, Adane Kassa; Castellazzi, Alberto; Delmonte, N.; Cova, P. (2016)
This paper presents the work on an alternative integration scheme for a half-bridge switch using 70 μm thin Si IGBTs and diodes addressing higher strength, higher toughness and higher thermal conductivity. The switch is totally bond wireless, since bonded wires increase self-heating and introduce further thermomechanical degradation mechanisms. Moreover, this solution is equipped with double side liquid cooling, and plug-in edge connectors both on the driver and load sides, allowing high power density, good accessibility and modularity. Preliminary experimental results show good switching behavior.